Nghiên cứu chế tạo vi sợi xenlulo từ sợi luồng ứng dụng làm vật liệu ép - Giang, Nguyễn Châu; Hoà, Tạ Thị Phương; Tùng, Nguyễn Huy (Vietnam Journal of Chemistry, 2012)
ABSTRACT Application of microfibrillated cellulose (MFC) in molding materials are broaden rapidly as it possesses very high strength, stiffness and biodegradable. Generally cellulose microfibrils were obtained from homogenization process of plant cell walls however a homogenizer costs a lot of money. The aim of our study was to develop an effective mean to extract microfibrillated cellulose from bamboo fiber and made it refined to each nano-level at laboratory scale. Long bamboo fibers were firstly applied with chemical treatment by using NaOH solution 1 N and HCl solution 1 N at 80oC. The treated and untreated bamboo fibers were then chemically analyzed for pentosan, lignin and cellulose contents to study the effect of chemical treatment process. After chemical treatment, the microfibrills were still associated within the cell walls however the cell wall structure has become loose because of removal of lignin and hemicelluloses. A mechanical treatment was applied to defibrillate them. A stone milling which often was used in traditional cake and noodle production was done for this purpose. This stone milling has successfully provided shear force that created the liberation of microfibrills from the cell walls. SEM micrographs of mechanical treated fiber showed improvement of degree of defibrillation with increasing in number of circles of stone milling and size of fiber has started to reduce submicron level. A novel polymer composite from received MFC was also fabricated.